1999
DOI: 10.1128/iai.67.5.2414-2420.1999
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Immunoglobulin Class and Immunoglobulin G Subclass Patterns against Ganglioside GQ1b in Miller Fisher Syndrome following Different Types of Infection

Abstract: We studied serum antibodies against gangliosides GQ1b and GM1 in 13 patients with Miller Fisher syndrome (MFS) and in 18 patients with Guillain-Barré syndrome (GBS) with cranial nerve involvement. Anti-GQ1b titers were elevated in all patients with MFS cases (immunoglobulin G [IgG] > IgA, IgM), and in 8 of the 18 with GBS. Lower frequencies of increased anti-GM1 titers were observed in MFS patients (3 of 13), as well as in GBS patients (5 of 18). During the course of MFS, anti-GQ1b titers of all Ig classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The IgG subclass of anti‐GM1 antibodies in GBS and anti‐GQ1b antibodies in FS are IgG1 or IgG3 . IgG3 is the major subclass of anti‐GQ1b antibodies in patients with FS after respiratory infection . A study of the IgG subclass of anti‐GM1 antibodies showed that the IgG1 subclass is associated with slow recovery and IgG3 with rapid recovery .…”
Section: Antiganglioside Antibodies In Guillain–barré Syndrome and Rementioning
confidence: 99%
“…The IgG subclass of anti‐GM1 antibodies in GBS and anti‐GQ1b antibodies in FS are IgG1 or IgG3 . IgG3 is the major subclass of anti‐GQ1b antibodies in patients with FS after respiratory infection . A study of the IgG subclass of anti‐GM1 antibodies showed that the IgG1 subclass is associated with slow recovery and IgG3 with rapid recovery .…”
Section: Antiganglioside Antibodies In Guillain–barré Syndrome and Rementioning
confidence: 99%
“…Our data indicate that there is not a specific subclass of anti-GD3 antibodies developed, although a significance difference is found for IgG4 in pregnant acutely infected patients. Previous findings in GBS show that anti-GM1 and anti-GT1a antibodies are predominantly IgG1 and IgG3 ( 30 ) and anti-GQ1b can either be IgG2 or IgG3, depending on the clinical manifestation ( 31 ). However, it has been described that the antibody response to GD3 in general is made of different subclasses of antibodies ( 32 ), these data are in line with our findings for adult acutely infected individuals.…”
Section: Discussionmentioning
confidence: 96%
“…These antibodies are directed against membrane ganglioside glycoprotein are found in high density on third, fourth, and sixth nerves. 48 Most patients with MF variant of GBS experience spontaneous recovery which is sometimes hastened by the administration of intravenous immunoglobulins or plasma exchange.…”
Section: Clinical Pearlmentioning
confidence: 99%